STUDI KAPASITAS DAN SINERGISME ANTIOKSIDAN PADA EKSTRAK KUNYIT (Curcuma domesticaVal.) DAN DAUN ASAM (Tamarindus indicaL.) - Riaminanti, Ni Kadek; Hartiati, Amna; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September, 2016)
The purpose of this study was 1) to know the effectratioof turmeric and tamarind leaf extract on antioxidant activity. 2) determinine ratioof turmeric and tamarind leaf that has the highest antioxidant activity and has the highest antioxidant synergism. This study used a randomized block design are three groups. Ratio of turmeric and tamarind leaf (100;0, 60;40, 55;45, 50;50, 45;55, 40;60, 0;100). The variables measure in this study  are : water content, total phenolic,antioxidant capacity, and vitamin C. The results showed that the ratio of turmeric and tamarind leaf has significant effect on all variables measured.Ratioof turmeric and tamarind leaf having the best is the treatment has highest antioxidant activity from ratio 55% : 45% turmeric and tamarind extract.Ratio extract 55% and 45% acid leaves the antioxidant capacity of 4,84 (mg GAEAC/100g extract), total phenolic 12.8 (mg GAE /100g extract), vitamin C 426(mg /100 g ), the water content of 22.9% and have highest synergism with value of 179.28%. Keywords: turmeric and tamarind, extraction, synergism antioxidant
Keywords: 110